Health‐care providers' concern regarding smoking cessation pharmacotherapies during pregnancy: Calls to a teratology information service. (26th January 2020) - Lee, Mei Lin; Tran, Duong T.; Welsh, Alec; Kennedy, Debra; Havard, Alys
Abstract: Introduction and Aims: Few smokers use smoking cessation pharmacotherapies during pregnancy. It is hypothesised that health‐care providers' reluctance due to safety concerns contributes to their low use. This study examined the extent of providers' concern regarding smoking cessation pharmacotherapies, relative to other medications in the same and other pregnancy risk categories. Calls made to a teratology information service (MotherSafe, Australia) were taken as a proxy indicator of concern regarding safety during pregnancy. Design and Methods: The primary exposure discussed in 66 687 calls made to MotherSafe between 2001 and 2016 was categorised as nicotine replacement therapy (NRT), bupropion, varenicline or category A (low risk), B1, B2, B3, C, D or X (teratogenic). Separate logistic regression models estimated the odds that calls regarding pharmacotherapies were from providers, relative to medications in the same and other risk categories. Models adjusted for caller remoteness and socio‐economic status. Results: Calls regarding bupropion were more likely to be made by providers than calls regarding other medications in its corresponding risk category [B2, adjusted odds ratio (aOR): 2.77, 95% confidence interval (CI) 1.17, 6.59]. Calls about varenicline were also more likely to be from providers than calls regarding other category B3 medications (aOR 95% CI 2.33:1.30, 4.17). Calls regarding NRT were not more or less likely to be from providers than calls regarding other category D medications. Discussion and Conclusions: Providers were more concerned about bupropion and varenicline than other medications within the same pregnancy risk categories. As this overestimation of risk may limit cessation pharmacotherapy use during pregnancy, research investigating strategies for correcting this imbalance is warranted.